Caracterização da liguagem oral em indivíduos com síndrome de Moebius - Barbosa, Renata Cavalcante (2003)
The Moebius syndrome constitutes a congenital disorder classically caused by generic factors. The syndrome is considered relevant for public health because of the increasing number of cases associated with the use of Cytotec® for abortion practice. This medication was originally marketed for the treatmait of peptic ulcer and contains misoprostol, a substance that acts on uterine contractility during pregnancy increasing the amplitude and frequency of uterine contractions, stimulating uterine bleedmg with partial or total expulsion of the fetus. The relation of these effects with the Moebius sequence is believed to be caused by the impact on brainstem vascularization caused by misoprostol leading to ischaemia with necrosis and occasional calcification of the facial nerve nucleus. Distinct patterns of inheraice has been suggested such as autosomal dominant, autosomal recessive and X-linked recessive. The gene responsible for the syndrome is still unknown although many researches suggest it's location next to the band ql2.2 of the chromosome 13 or on the chromosome itself. The clinical manifestations include lesion of the facial and abducens nerves associated with limb malformations, specially club foot. The presence of phenotypic variation is also expected, secondary to the compromise of the other cranial nerves, mamly bulbar. In this way, a great range of malformations has been identified, including tongue and/or pharynx paralysis, absent pectoral muscles, syndactyly with or without pectoral muscle absence (Poland syndrome), bulbar involvement, hypoglossia-hypodactyly syndrome (Hanhart syna'ome) and, occasionally, mental retardation. The speech-language manifestations include compromise of oral and deglutition, speech and language functions, secondary to cranial nerves lesions and mental retardation. The language compromise in this disorder is still not well known. In this way, the main objective of this study is to characterize the oral language in a population of fifteen subjects with Moebius syndrome with age ranging from two to thirteai years old, from both sexes, seen in one of the three main center for genetic diagnosis in the state of Ceará. The present work is a descriptive study of a cross-sectional design conducted from February to December/2002, using a clinical evaluation of language components including morphology, syntax, semantics and pragmatics. The results showed mean age of seven years and five months with greater prevalaice of males (53,3%), limb involvement in 93.3% of the study population, mainly club foot. Craniofacial involvement occurred in all individuals and facial nerve paralysis, strabismus and micrognathia were the most prevalait. High occurrence of report of abortion tentative with the use of Cytotec® was identified. All subjects that reported this practice used Cytotec® (10/10). The administration route most used was the combined, oral and vaginal (70%), with the use of two tablets (90%) during the first tnmester of pregnancy in all cases. We idaitified exclusive speech involvement in 20% of the subjects, language disturbance in 46.7%, speech and language disturbance in 13.3% and oral language involvement in 26,7%. Based on our evidence we conclude that the language disturbance in the Moebius syndrome presents with a variable compromise of all oral language components mainly phonological, morphological and syntactical abilities. The delay in linguistical development, incomprehensive speech and the deficit of constructions of saliences and narrations are constant.